Solutions for atypical problems in the incisors area: a transdisciplinary challenge - Márcio Costa Sobral
ABSTRACT Introduction: A significant increase in the number of adults in search of orthodontic treatment has raised a new challenge for orthodontists: the need to interact with other specialties to achieve excellent results, particularly when dealing with smile aesthetics and facial balance. Several factors should be considered to respond to their demand: adequate tooth leveling and alignment, individual tooth proportions between adjacent teeth and their contralateral teeth, shape and natural appearance of each tooth and gingival architecture, which should all be in agreement with facial harmony. Maxillary or mandibular incisors congenitally missing or lost due to caries or trauma and tooth-size discrepancies (Bolton) are some of the important aesthetic challenges for an integrated orthodontic treatment. Objectives: This study describes cases that illustrate the clinical challenges of treating the anterior area, as well as the multidisciplinary strategies required for their resolution. Conclusion: The increasingly frequent multidisciplinary orthodontic treatments of complex cases seem to effectively maximize aesthetic and functional results using a combination of procedures conducted by specialists in related areas, such as Surgery, Prosthetics, Implantology, Restorative Dentistry and Periodontics.